Temporary overpessimism: Job loss expectations following a large negative employment shock - Julian Emmler; Bernd Fitzenberger (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2021)
Job loss expectations were widespread among workers in East Germany aftfter reunification with West Germany. Though experiencing a large negative employment shock, East German workers were still overpessimistic immediately aftfter reunification with respect to their job risk. Over time, job loss expectations fell and converged to West German levels, which was driven by a stabilizing economic environment and by an adaptation of the interpretation of economic signals with workers learning to distinguish individual risk from firm level risk. In fact, conditional on actual job loss risk, East German workers quickly caught up to West Germans regarding the accuracy of job loss expectations. – – In den Jahren nach den Wiedervereinigung mit Westdeutschland erwartete ein großer Anteil der Ostdeutschen Arbeitnehmer ihren Job zu verlieren. Zwar führte der Wiedervereinigungsschock zu einem substantiell erhöhten Risiko des Arbeitsplatzverlusts in Ost- im Vergleich zu Westdeutschland, die Erwartungen der Ostdeutschen Arbeitnehmer waren jedoch noch negativer und somit zu pessimistisch. Im Laufe der Zeit fiel jedoch die Zahl der erwarteten Arbeitsplatzverluste und konvergierte zum Westdeutschen Niveau, getrieben zum einen durch die sich stabilisierende wirtschaftliche Lage in Ostdeutschland und zumanderen durch einen Lernprozess der Arbeiter im Bezug auf die Trennung von individuellem und firmenspezifischen Risiko. Bedingt auf das wirkliche Risiko den Job zu verlieren schlossen Ostdeutsche Arbeitnehmer schnell zu Westdeutschen Arbeitnehmern auf.
Keywords: D84; J64; J63; P20; 330; job loss; expectations; transition economies